Processing routes for graphene composites - Roslan, Muhammad Sufi; Mat Zian @ Mat Zin, Ahmad Faiz; Abd Rahman, Misbahul Muneer; Makminin, Suhaimi (Penerbit UTHM, 2020)
Graphene feature exceptional electrical, thermal, and mechanical properties as well thus have been extensively considered as functional or reinforcing composite. The inclusive performance of the composite is determined by graphene microstructures which are related to the sp2 hybridization of graphene structure as well as pristine or modified interaction with matrix materials.